If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2T + 3 = 5 + -2T + 6 Reorder the terms: 3 + 2T = 5 + -2T + 6 Reorder the terms: 3 + 2T = 5 + 6 + -2T Combine like terms: 5 + 6 = 11 3 + 2T = 11 + -2T Solving 3 + 2T = 11 + -2T Solving for variable 'T'. Move all terms containing T to the left, all other terms to the right. Add '2T' to each side of the equation. 3 + 2T + 2T = 11 + -2T + 2T Combine like terms: 2T + 2T = 4T 3 + 4T = 11 + -2T + 2T Combine like terms: -2T + 2T = 0 3 + 4T = 11 + 0 3 + 4T = 11 Add '-3' to each side of the equation. 3 + -3 + 4T = 11 + -3 Combine like terms: 3 + -3 = 0 0 + 4T = 11 + -3 4T = 11 + -3 Combine like terms: 11 + -3 = 8 4T = 8 Divide each side by '4'. T = 2 Simplifying T = 2
| 15h-24=36 | | 49=12+x/7 | | -60=-5x+5(-x+10) | | 4y+16=24 | | 9k^2= | | 7(-3+x)=4(3-x) | | M+4=2M-3 | | 5t^2+45k=0 | | 3a^2-6a+8+6a^2-4+2a^2-a+12= | | 9m^2-88m+63=0 | | 5+4x=x-4 | | 117=2x+15 | | 2(x-4)=6(x+2) | | 3g+1=3 | | 117=2x+y | | 3/4(x-2)+3/5-1/5(x+1) | | -106=2x-6(x+11) | | 2x-2=900 | | 1=(117-x)/2 | | (x/8)-6=5 | | y/7-6=11 | | 16-q/11=9 | | 9e^6x/3e^4x | | -4x-5(-2x-14)=22 | | f(x)=2x^2-4x-2 | | 4(X-3)=6X+4(X+3) | | 2x*2x=(x+10)(2x-3) | | 4(X-3)=6X+4(X-3) | | -10-6x=-4x+22 | | 10-6x=-4x+22 | | -100=-5g | | -8(6x+18)=144 |